Assembling frameworks for strategic innovation enactment: Enhancing transformational agility through situational scanning - Joel Bigley (Administrative Sciences, 2018)
Although a significant body of knowledge has been created around strategic management that drives change and innovation, there are voids in the literature regarding assembling a flexible and localized environmental scanning (ES) framework needed to assess threats, opportunities, the current environment, and the desired end-state of a global value chain (GVC) with direct linkages to strategic enactment. In this paper, the author describes this gap and develops a capability to create a task plan from a situational ES. The need for ES customization is further validated as a result of the change during a transformation or adaptation, hence the need for a localized feedback mechanism.
Keywords: 350; environmental scan; situational agility; global value chain; localized strategy; strategic agility